Ways of talking about drawing practices. Sociocultural views: Gombrich and visually controlled drawing - Frisch, Nina Scott (FormAkademisk, 2011)
In this article, I explore how part of the culture historian professor Ernst Gombrich’s vocabulary can be used in two examples of today’s drawing processes among children (age 9–12). His terms are related to their possible theoretical origin and placed in sociocultural understandings of human activity—and contrasted with other possible useful terms in a drawing-teaching context. How terms can encourage various teaching practices is then discussed.